INFLUENCE OF TRUST, SECURITY, COMPLETENESS, AND MARKETING ON PURCHASING DECISIONS OF BANDUNG INSTITUTE OF TECHNOLOGY STUDENTS AT TOKOPEDIA - Fatikha Aristantri, Quinta
Technology in Indonesia is developing rapidly from year to year, the COVID-19 pandemic that affect the world triggered changes to the habits of Indonesian People. Everything and anything is now available online and one of the frequent thing that almost everyone do online is shopping. There are several ecommerce company in Indonesia, one of the biggest company is Tokopedia. In order to choose a marketplace to do online shopping (e-commerce), there must be some considerations based on factors that influence purchasing decisions. These factors include trust, security, completeness, and marketing on purchasing decisions of students at Bandung Institute of Technology at Tokopedia. This study aims to obtain a mathematical model of the influence of trust, security, completeness, and marketing on purchasing decisions of students at Bandung Institute of Technology at Tokopedia. This study analyse what are the factors that influence purchasing decisions at Tokopedia for Bandung Institute of Technology students using Multiple Linear Regression. In this study, the independent variables consist of Trust (????!), Security (????"), Completeness (????#), and Marketing (????$) with the dependent variable Purchasing Decision (????). This final project started by collecting data using a questionnaire with questions of the 5-point Likert Scale method. Then a descriptive statistics are processed from the result of the questionnaire. From the correlation matrix, it can be seen that the independent variables that has the tightest relationship with the dependent variable are trust (????!) and marketing (????$). The validity test and reliability test was conducted with the result of all questions are valid and all variables are reliable. Multiple linear regression then performed for 11 (eleven) combinations of variables, models combining 4 (four) independent variables with 1 (one) dependent variable, models combining 3 (three) independent variables with 1 (one) dependent variable, and models combining 2 (two) independent variables with 1 (one) dependent variable. In multiple linear regression analysis, partial hypothesis testing was performed, to determine the effect of each variable in the model partially, and simultaneous hypothesis testing was also performed, to determine the effect of independent variables in the model simultaneously on dependent variable. The results of multiple linear regression analysis was obtained related to the partial influence, simultaneous influence, and influence of the variables in the model through the Adjusted R Square value. By comparing all combinations of variables, multiple linear regression model was selected which had influence on the model. And out of all variables in the model, the variables that had partial effect is the regression model with independent variables of trust (????!) and marketing (????$). The classical regression assumption tests are conducted for the model selected, which are the multicollinearity test, residual normality test, and heteroscedasticity test. The results of the classical regression assumption tests for the regression model with independent variables of trust (????!) and marketing (????$) are that there is no multicollinearity, has normal distribution of residuals, and does not occur heteroscedasticity. So, the model is a good linear regression model. Therefore, based on the results of this final project, it was concluded that the mathematical model of the influence of trust, security, completeness, and marketing on purchasing decisions at Tokopedia was Y = 0.207 + 0.353????! + 0.320????$ and the factors that have the most influence on purchasing decisions are trust and marketing with the influence of 43% (forty-three percent).